Why the English school needs conflict studies: Retheorising the place of war in international society. Issue 1 (28th January 2021) - Lees, Nicholas
Abstract: The English School tradition offers a compelling framework for understanding war as an institution within an international society constructed by states. Nonetheless, analyses of the causes of inter-state insecurity offered by English School scholars are underspecified and fail to develop distinct middle-range theories based on these core insights. These problems can be remedied through an engagement with the subfield of quantitative conflict studies. This pairing of 'scientific' and 'classical' research traditions seems improbable, but the methodological barriers to conversation can be overcome if claims about the circumstances and causes of war are contextualised historically. Important findings in conflict research vindicate the English School understanding of war as a social institution of an anarchical society and a norm-governed mechanism for resolving disputes between political entities. Further dialogue between these approaches would deepen our understanding of how the global institutional landscape shapes both war and peace.